Symptomatic mucosal involvement in pachyonychia congenita: challenges in infants and young children. (1st March 2020) - Goldberg, I.; Mashiah, J.; Kutz, A.; Derowe, A.; Warshauer, E.; Schwartz, M.E.; Smith, F.; Sprecher, E.; Hansen, C.D.
Summary: Background: Pachyonychia congenita (PC) is a rare autosomal dominant genodermatosis caused by a mutation in any one of five keratin genes ( KRT6A, KRT6B, KRT6C, KRT16 or KRT17 ). Characteristic features of PC are painful palmoplantar keratoderma, variable nail dystrophy, cysts, follicular hyperkeratosis and often oral leukokeratosis. Although oral leukokeratosis can go unnoticed, mucosal involvement of the oral cavity and upper airways can manifest with pain during feeding, hoarseness, stridor and, occasionally, life‐threatening obstruction. Objectives: To characterize patients with PC with symptomatic mucosal involvement. Methods: We present a case series of nine children with PC with symptomatic mucosal involvement, all with heterozygous mutations in KRT6A . Seven patients complained of painful feeding problems. Four patients were diagnosed with failure to thrive, three of whom required a feeding tube. Simple feeding solutions were beneficial in most cases. Seven patients had laryngeal involvement and one patient died at 4 years of age from acute laryngeal obstruction. Conclusions: It is important for dermatologists and otolaryngologists to be aware that symptomatic mucosal involvement, and very rarely laryngeal obstruction, can occur in patients with PC. Usually simple feeding solutions may prevent complications and failure to thrive. What's already known about this topic? Pachyonychia congenita (PC) is a rare autosomal dominant genodermatosis due to a mutation in any one of five keratin genes. Symptomatic mucosal involvement is an important clinical feature of PC and appears to be more pronounced in KRT6A mutation carriers. Only leukokeratosis is frequently seen in PC and can be one of the earliest signs of disease. Laryngeal involvement is a less common feature. It might be symptomatic but usually presents as hoarseness, stridor and, occasionally, as a life‐threatening respiratory distress. What does this study add? In most cases of laryngeal involvement, there is no need for any intervention. Although pain and feeding difficulties are usually attributed to the oral leukokeratosis, they can be related to a phenomenon called 'first bite syndrome' (FBS). Symptomatic mucosal involvement with feeding difficulty is important but can be managed in most cases with simple feeding solutions (e.g. softer nipple with a larger hole, thicker formula and feeding with a syringe). Linked Comment: Youssefian and Vahidnezhad. Br J Dermatol 2020; 182 :536–537 .